Interaksi Simbolik untuk Akuntansi Sektor Publik - Razak, A. (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
This research is important, especially to explore further the behavioral aspects behind the budget. Researchers want to get a more real and definite picture of who is behind the power in the process of preparing the Regional Government budget. how their life and behavior; how they think and make decisions; as well as other people around them. All of these aspects may very well influence the behavior of the executive and legislature in the practice of decision-making in the process of drafting the Regional Government budget that has been running so far. Based on the problems above, the goal to be achieved is